1913
DOI: 10.5962/bhl.title.3917
|View full text |Cite
|
Sign up to set email alerts
|

The British rust fungi (Uredinales) their biology and classification

Abstract: NATURE OF THE SPERMATIA circumstances, would shew quick and luxuriant growth : tln-v cannot be degenerate conidia, because the nucleus is large and well-formed though at times no nucleolus can be seen.(5) Poaeon Poa. Race 1 grows not only on Rye, but also on Hordeum vulgare, H. murinum, Agropyron repens, A. caninum, Elymus arenarius, Bromus secalinus etc. (In all these enumerations non-British species will be omitted.) Race 2, on Oat, and on Arrhenatherum elatius, Dactylis glomerata, Alopecurus pratensis, Mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…However, measurements of the concentration of 7chlortetracycline after incubation in "basic" medium with and without the presence of the dye by the method of Grove & Randall (1955), showed no loss of the antibiotic due to the presence of the dye, and, after growth in medium containing dye, the organisms grew readily in "basic" medium in the absence of dye and were still completely unaffected by normally bacteriostatic concentrations of the tetracyclines. There are three possible explanations: (1) the dye caused a rapid alteration of the tetracyclines to inactive forms ; (2) the dye itself was used as a by-pass to the parts of the system which are affected by tetracyclines ; (3) growth in the presence of the dye resulted in the development of alternative metabolic routes which were not susceptible to the tetracyclines.…”
Section: Primary Sites Of Inhibition By Tetracyclinesmentioning
confidence: 98%
“…However, measurements of the concentration of 7chlortetracycline after incubation in "basic" medium with and without the presence of the dye by the method of Grove & Randall (1955), showed no loss of the antibiotic due to the presence of the dye, and, after growth in medium containing dye, the organisms grew readily in "basic" medium in the absence of dye and were still completely unaffected by normally bacteriostatic concentrations of the tetracyclines. There are three possible explanations: (1) the dye caused a rapid alteration of the tetracyclines to inactive forms ; (2) the dye itself was used as a by-pass to the parts of the system which are affected by tetracyclines ; (3) growth in the presence of the dye resulted in the development of alternative metabolic routes which were not susceptible to the tetracyclines.…”
Section: Primary Sites Of Inhibition By Tetracyclinesmentioning
confidence: 98%
“…Grove also communicated his findings to the Académie des Sciences in Paris, which Antoine Henri Becquerel (1852-1908; 1903 Nobel Prize for Physics) read in its session of April 15, 1839 (Grove, 1839a). The publications were followed by a large number of others describing new electrochemical findings, improvements of the original cell, molecular composition and decomposition (Grove, 1839e, 1843b(Grove, 1839e, , 1844a, the electrochemical decomposition and synthesis of water (Grove, 1839b(Grove, , 1843ce, 1846a(Grove, , 1847bc, 1853, discovery of polarization (Grove, 1839d), electrical conductivity by flames (Grove, 1854), today's fuel cell (Grove, 1842b(Grove, , 1845a, Daguerreotype plates (Grove, 1843d), photography (Grove, 1844b), voltaic action on phosphorus, sulfur, and hydrocarbons (Grove, 1845c), of black bands (striae) in electrical breakdown (Grove, 1858(Grove, , 1858(Grove, -1862.…”
Section: Introductionmentioning
confidence: 99%
“…They are not shed, but remain on the leaf and germinate without dormancy (Wilson & Henderson, 1966). Then the basidiospores produced infect new leaves (Grove, 1913). Durrieu (2001) reported that P. buxi is common on wild box tree in Central and south-western Europe but is absent in the Pyrenees mountains and in Spain, where the host grows without tree cover.…”
mentioning
confidence: 99%